2020
DOI: 10.1038/s41419-020-02999-5
|View full text |Cite
|
Sign up to set email alerts
|

Mutual regulation between OGT and XIAP to control colon cancer cell growth and invasion

Abstract: O-GlcNAc transferase (OGT) is an enzyme that catalyzes the O-GlcNAc modification of nucleocytoplasmic proteins and is highly expressed in many types of cancer. However, the mechanism regulating its expression in cancer cells is not well understood. This study shows that OGT is a substrate of the E3 ubiquitin ligase X-linked inhibitor of apoptosis (XIAP) which plays an important role in cancer pathogenesis. Although LSD2 histone demethylase has already been reported as an E3 ubiquitin ligase in lung cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…In this study, we identified the aberrantly elevated expression of OGT and OGA as a consequence of KU60019 treatment in SKOV3 cells. These results are consistent with studies on colon cancer ( 31 ), intestinal tumorigenesis ( 32 ), and other types of tumorigeneses. Significant cell death was also found in SKOV3 cells after ATM inhibition, indicating a potential correlation between cell viability and energy metabolism-related genes.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we identified the aberrantly elevated expression of OGT and OGA as a consequence of KU60019 treatment in SKOV3 cells. These results are consistent with studies on colon cancer ( 31 ), intestinal tumorigenesis ( 32 ), and other types of tumorigeneses. Significant cell death was also found in SKOV3 cells after ATM inhibition, indicating a potential correlation between cell viability and energy metabolism-related genes.…”
Section: Discussionsupporting
confidence: 92%
“…A number of E3 UB ligases have been reported to interact with OGT and regulate its activity in the cell. In addition to histone methyltransferase, LSD2 and Ring E3 XIAP that have been shown to ubiquitinate OGT in reconstituted ubiquitination assays in vitro and in the cell [ 10 , 11 ]. β-TrCP, a substrate adaptor of the Skp1–Cullin–F-box-protein (SCF) E3, was found to destabilize OGT in the cell, although the ubiquitination of OGT catalyzed by the SCF complex bridged by β-TrCP is yet to be confirmed [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This would enable UB transfer from LSD2 to OGT and induce the degradation of OGT [ 10 ]. Recently, Ring E3 XIAP was found to recognize OGT as a ubiquitination target and signal its degradation by the proteasome [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of their outstanding capacity to regulate cell death along with their high expression in many types of tumor cells, IAPs may be a new target for cancer therapy in the future. Increasing evidence suggests that suppression of XIAP can inhibit tumor growth in gastric cancer [ 38 ], prostate cancer [ 39 ], colon cancer [ 40 ], and HCC [ 41 ]. In this study, XIAP could bind with miR-212-3p and mechanistically antagonize the inhibitory effect of miR-212-3p on carcinogenesis, indicating that XIAP is likely to be associated with tumorigenesis and enhance the malignant behavior of HCC cells, which is consistent with the results of 41 [ 41 ].…”
Section: Discussionmentioning
confidence: 99%